Screening tests are not enough to detect hemineglect Testes de triagem não são suficientes para diagnosticar heminegligência - Manuel Alvim Leite Lopes; Hebert Pereira Ferreira; Juliana Costa Carvalho; Lídia Cardoso; Charles André (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To verify the sensitivity of the conventional subtests of the Behavioral Inattention Test (BIT) in the diagnosis of hemineglect after stroke. METHOD: One hundred and two patients with cerebral infarct or hemorrhage were prospectively evaluated. In 22, hemineglect was diagnosed using standard BIT criteria. The frequency of hemineglect using 6 commonly used screening subtests of this battery was assessed. RESULTS: Hemineglect would not be recognized in 10 patients if they were only screened using the line crossing test; this would be the case in 2 patients with the letter cancellation test; and in 4 patient with the line bisection test. Three patients would not be diagnosed even if both line crossing and line bisection tests were used. CONCLUSION: Hemineglect may not be recognized with single screening tests commonly used. The use of a standard battery is recommended to improve diagnostic sensitivity in individuals with various subtypes of hemineglect. OBJETIVO: Verificar a sensibilidade dos subtestes convencionais da Behavioral Inattention Test (BIT) no diagnóstico da heminegligência após o acidente vascular cerebral (AVC). MÉTODO: Foram avaliados prospectivamente 102 pacientes com AVC. Em 22 casos heminegligência foi diagnosticada através do BIT. A freqüência de diagnóstico correto utilizando os 6 subtestes específicos desta bateria foi analisada. RESULTADOS: 10 pacientes não seriam diagnosticados como heminegligentes se fossem avaliados apenas com o " line crossing" , 2 se o teste de triagem escolhido fosse o " letter cancellation" , e 4 se utilizássemos apenas o " line bisection" . Além disso, 3 pacientes não teriam recebido o diagnóstico correto mesmo utilizando dois testes usuais de triagem - " line crossing" e " line bisection" . CONCLUSÃO: O uso de testes isolados de triagem pode falhar em diagnosticar heminegligência após o AVC. O uso de uma bateria formal de avaliação é necessário para identificar indivíduos com diferentes tipos de heminegligência.